2020
DOI: 10.1371/journal.pcbi.1008075
|View full text |Cite
|
Sign up to set email alerts
|

Electrical coupling controls dimensionality and chaotic firing of inferior olive neurons

Abstract: We previously proposed, on theoretical grounds, that the cerebellum must regulate the dimensionality of its neuronal activity during motor learning and control to cope with the low firing frequency of inferior olive neurons, which form one of two major inputs to the cerebellar cortex. Such dimensionality regulation is possible via modulation of electrical coupling through the gap junctions between inferior olive neurons by inhibitory GABAergic synapses. In addition, we previously showed in simulations that int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 108 publications
(201 reference statements)
1
14
0
Order By: Relevance
“…One may also expect that there are no common inputs across TC populations so that the electrical couplings remain decoupled among them. Together, as indicated by previous theoretical and experimental studies 15, 33, 39, 41, 46, 83, 84 , these results suggest that common inputs and positive feedback to IO cells are the key structures that organize neuron populations, induce changes in their cue responsiveness, resulting in changed behavior. Because synchronization within components is larger than synchronization across components and anatomical zones, and because even individual neurons multiplex several components, we suggest that components self-organize 8587 as a result of interaction between electrical synapses in the IO and positive feedback and lateral inhibition implemented by loop dynamics between PC, CN, and IO (Fig 7A).…”
Section: Discussionsupporting
confidence: 79%
“…One may also expect that there are no common inputs across TC populations so that the electrical couplings remain decoupled among them. Together, as indicated by previous theoretical and experimental studies 15, 33, 39, 41, 46, 83, 84 , these results suggest that common inputs and positive feedback to IO cells are the key structures that organize neuron populations, induce changes in their cue responsiveness, resulting in changed behavior. Because synchronization within components is larger than synchronization across components and anatomical zones, and because even individual neurons multiplex several components, we suggest that components self-organize 8587 as a result of interaction between electrical synapses in the IO and positive feedback and lateral inhibition implemented by loop dynamics between PC, CN, and IO (Fig 7A).…”
Section: Discussionsupporting
confidence: 79%
“…Instead, to allow comparison between varying experimental conditions and event amplitudes, we present the fluorescence intensities in units of power (fW), estimated based on photo-conversion properties of camera sensors (using a window between dark noise and full electron-saturated pixel). Obviously, future studies may employ advanced mathematical approaches (such as Hoang et al, 2020 ) to increase precision of desired measurements, but they need to be carefully designed for the question at hand.…”
Section: Discussionmentioning
confidence: 99%
“…Despite several works having employed a generic targeting approach for IO (White and Sillitoe, 2017 ; Rowan et al, 2018 ; Gaffield et al, 2019 ; González-Calvo et al, 2021 ), no systematic effort has been made to create a more specific targeting tool. Instead, experimenters have resorted to indirect methods, such as imaging IO-axon-evoked spikes in the cerebellum (Ju et al, 2019 ; Hoang et al, 2020 ; Roh et al, 2020 ; Michikawa et al, 2021 ), optogenetic modulation of IO afferents instead of IO neurons (Kim et al, 2020 ), limiting experimentation to cerebellar cortical regions where off-target transfection of axons with, e.g., the CamKII promoter is not problematic (Mathews et al, 2012 ; Gaffield et al, 2019 ) or morphological analysis (Nishiyama et al, 2007 ; Pätz et al, 2018 ; Vrieler et al, 2019 ; González-Calvo et al, 2021 ). To our knowledge, there have been no published reports of in situ, in vivo multi-cell IO network activity besides our recently-published preliminary observations (Guo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a selective disruption of the long loop disorganizes the online operation of cerebellar forward model and leads to manifestation of irregular tremors, including kinetic tremor in Holmes' classic study and intention tremor, when the dysfunction exceeds a threshold. We also hypothesize that the disruption of the short loop (i.e., removal of inhibition on the gap junctions between IO neurons) shifts IO activities toward the synchronous mode like a local injection of bicuculine into IO ( 85 ) to cause regular tremors such as regular postural tremor in Holmes' classic study.…”
Section: Section II Physiological Backgrounds Of Two Types Of Cerebellar Tremorsmentioning
confidence: 95%
“…Therefore, CS activities are corrupted by increased noise (i.e., low S/N ratio) during regular tremors. Second, Hoang et al ( 85 ) recently found that high coupling strengths of IO neurons induce their synchronous firing and decrease the amount of information encoded by firing dynamics of IO neurons. The two mechanisms may gradually deteriorate the forward model and increase its prediction error, resulting in irregular tremor.…”
Section: Section II Physiological Backgrounds Of Two Types Of Cerebellar Tremorsmentioning
confidence: 99%